Temporal and spatial distribution of ferredoxin isoproteins in tomato fruit. - Aoki, K (1996)
Five ferredoxin (Fd) isoproteins (FdA, FdB, FdC, FdD, and FdE) were isolated from tomato (Lycopersicon esculentum cv Momotaro) fruit. These isoproteins showed differential temporal and spatial accumulation patterns. FdA and FdC were present in leaves. FdE was present in roots, and FdB and FdD were fruit-specific. During fruit growth, the relative abundance of FdA decreased and that of FdE increased. The FdE/FdA ratio was higher in the inner tissues of the fruit than in the outer tissue, and it was correlated with starch accumulation. In darkgrown fruit the contents of FdA, FdB, and FdC, as well as chlorophyll, decreased remarkably relative to their light-grown counterparts; however, the contents of FdE and starch did not change significantly. Under in vitro conditions FdE showed higher cytochrome c reduction activity than FdA and FdB. These results, together with their N-terminal sequences, indicate that both photosynthetic- and heterotrophic-type Fd isoproteins are present in tomato fruit.